Mindfulness Sitting: Enhancing Students’ Listening Skill at Jinarakkhita Buddhist College Lampung - Ayu Andriyaningsih; Ismoyo, Tejo; Susanto, Susanto; Juni Suryanadi (LPPM STIAB JINARAKKHITA LAMPUNG, 2023)
The ancient contemplative traditions that gave rise to the practice of mindfulness have attracted a lot of interest recently because of their potential to improve many facets of human well-being. A fascinating field of study is the connection between mindfulness sitting and attentive listening abilities. In this research, the researcher explore the possible impact of mindful sitting on the growth and improvement of good listening techniques. This study aims to examine the effect of mindfulness sitting on listening skill. The researcher used a pretest-posttest experimental group design. The research used the Statistical Package for Social Science (SPSS) to analyze the data. A rubric score used to analyze and measure the students’ listening skill before and after treatment. The students’ listening skill improved from 30.7 to 77.1. In addition, the researcher found that students who struggled in listening comprehension now have a grow understanding in their listening skill. Therefore, it is important to use mindfulness method to improve listening achievement.